The Hebrew Bible : A Critical Companion - Barton, John, 1948- (Book collections on Project MUSE., 2016)
This book brings together some of the world's most exciting scholars from across a variety of disciplines to provide a concise and accessible guide to the Hebrew Bible. It covers every major genre of book in the Old Testament together with in-depth discussions of major themes such as human nature, covenant, creation, ethics, ritual and purity, sacred space, and monotheism. This authoritative overview sets each book within its historical and cultural context in the ancient Near East, paying special attention to its sociological setting. It provides new insights into the reception of the books and the different ways they have been studied, from historical-critical enquiry to modern advocacy approaches such as feminism and liberation theology. It also includes a guide to biblical translations and textual criticism and helpful suggestions for further reading. Featuring contributions from experts with backgrounds in the Jewish and Christian faith traditions as well as secular scholars in the humanities and social sciences, The Hebrew Bible is the perfect starting place for anyone seeking a user-friendly introduction to the Old Testament, and an invaluable reference book for students and teachers.